Bunnicula : Bunnicula Series #1 - Howe, Deborah; Howe, James, 1946-; Daniel, Alan, 1939- (New York : Atheneum, 1979)
Though scoffed at by Harold the dog, Chester the cat tries to warn his human family that their foundling baby bunny must be a vampire.
Keywords: Rabbits -- Fiction; Vampires -- Fiction; Mystery and detective stories; Rabbits -- Fiction -- Juvenile literature; Rabbits -- Fiction; Vampires -- fiction; Howe, James -- jt. auth; Daniel, Alan -- illus; Mystery fiction